Numerical simulation of two-phase flow in 4x4 simulated bundle - Ayako ONO (The Japan Society of Mechanical Engineers, 2020)
An evaluation methodology of a thermal-hydraulics based on a mechanism in light water reactors (LWRs) is needed from a viewpoint of the safety analysis during normal operation and unanticipated transient such as under a severe accident. Currently, the evaluation of safety for the nuclear reactor has been implemented by a best estimate (BE) code and subchannel analysis code. These analysis codes contain models and empirical correlations. Therefore, the full-scale mock-up tests are needed to evaluate the reliability and validation of code. And the model and empirical correlation are allowed to be applied only in the range where the experiments were implemented. The large mock-up tests are once again needed in order to consider the new geometry and boundary conditions when the design of components is changed. Hence, the 3D detailed numerical simulation by the mechanistically based method is expected to be applied for the preliminary analysis to improve the design of fuel assemblies and evaluate the safety. This 3D detailed numerical simulation can reduce the large mock-up tests. The detailed numerical simulation method can provide much information relating to the two-phase flow such as the bubble size, its velocity, and detailed void distribution which, for example, are needed to predict the critical heat flux based on the mechanism. Moreover, JAEA is implementing the development of the nuclear-thermal-coupling code by using a detailed two-phase flow analysis code based on the VOF method like a JUPITER code. In this study, the numerical simulation of two-phase flow in the 4x4 bundle was examined by numerical simulation code JUPITER in order to examine the possibility of the JUPITER code for the large scale two-phase flow analysis. The simulation results are verified by the previous experimental data of two-phase flow.